Functional Knee Score in Knee Osteoarthritis with Tibial Defect Performed Total Knee Arthroplasty with Screw Augmentation - Gardjito, Fajar Baskoro; Perdana, Arief Indra; Mariyanto, Ismail; Idulhaq, Mujaddid; Utomo, Pamudji (Indonesian Journal of Medicine, 2018)
Background: Long-standing knee osteoarthritis also is a common cause of severe bone deficiency (especially proximal tibia). Total knee arthroplasty is indicated in patient with knee osteoarthritis who did not able to perform activity daily living. This study aimed to evaluate the functional knee score of the patient with knee osteoarthritis who performed total knee arthroplasty with screw augmentation.Subjects and Method: This was an analytic observational study conducted at Soeharso Orthopaedic Hospital, Surakarta, Central Java, from January to December 2016. A sample of 30 patients with knee osteoarthritis with tibial defect who performed total knee arthroplasty with screw augmentation was selected for this study. The dependent variable was functional knee score. The independent variable was knee arthroplasty with screw augmentation. Knee function was measured by knee society score. The difference of knee function score between before and after total knee arthroplasty with screw augmentation was analyzed by t test.Results: There were 30 patients (25 females and 5 males) with age between 54 to 73 years old. Mean of knee society score post operative (mean= 82.7; SD= 6.29) was higher than pre operative (mean= 30.5; SD= 6.74) and it was statistically significant (p=0.001).Conclusion: Knee society score after total knee arthroplasty with screw augmentation is higher than before surgery.Keywords: functional knee score, osteoarthritis, screw augmentationCorrespondence: Fajar Baskoro Gardjito, Department of Orthopaedic and Traumatology, Faculty of Medicine, Universitas Sebelas Maret/Dr. Moewardi Hospital/Prof. Dr. R. Soeharso Orthopaedic Hospital. Email: baskovic9237@gmail.com.Indonesian Journal of Medicine (2018), 3(3): 134-138https://doi.org/10.26911/theijmed.2018.03.03.02